New and Promising Chemotherapeutics for Emerging Infections Involving Drug-resistant Non-albicans Candida Species - Silva, Laura N.; de Mello, Thaís Pereira; de Souza Ramos, Lívia; Branquinha, Marta Helena; dos Santos, André L. S. (Current Topics in Medicinal Chemistry, 2019)
Fungal infections are a veritable public health problem worldwide. The increasing number of patient populations at risk (e.g. transplanted individuals, cancer patients, and HIV-infected people), as well as the use of antifungal agents for prophylaxis in medicine, have favored the emergence of previously rare or newly identified fungal species. Indeed, novel antifungal resistance patterns have been observed, including environmental sources and the emergence of simultaneous resistance to different antifungal classes, especially in Candida spp., which are known for the multidrug-resistance (MDR) profile. In order to circumvent this alarming scenario, the international researchers’ community is engaged in discovering new, potent, and promising compounds to be used in a near future to treat resistant fungal infections in hospital settings on a global scale. In this context, many compounds with antifungal action from both natural and synthetic sources are currently under clinical development, including those that target either ergosterol or β(1,3)-D-glucan, presenting clear evidence of pharmacologic/pharmacokinetic advantages over currently available drugs against these two well-known fungal target structures. Among these are the tetrazoles VT-1129, VT-1161, and VT-1598, the echinocandin CD101, and the glucan synthase inhibitor SCY-078. In this review, we compiled the most recent antifungal compounds that are currently in clinical trials of development and described the potential outcomes against emerging and rare Candida species, with a focus on C. auris, C. dubliniensis, C. glabrata, C. guilliermondii, C. haemulonii, and C. rugosa. In addition to possibly overcoming the limitations of currently available antifungals, new investigational chemical agents that can enhance the classic antifungal activity, thereby reversing previously resistant phenotypes, were also highlighted. While novel and increasingly MDR non-albicans Candida species continue to emerge worldwide, novel strategies for rapid identification and treatment are needed to combat these life-threatening opportunistic fungal infections.
Keywords: Azoles